Primary neuroendocrine carcinoma of the brain. Issue 9 (18th September 2019) - Reed, Clay T; Duma, Narjust; Halfdanarson, Thorvardur; Buckner, Jan
Abstract : Neuroendocrine neoplasms (NENs) are malignancies with rare reports of central nervous system development. A 34-year-old woman was found to have a primary NEN of the brain, and she had recurrence with identical histology 10 years later. Extracranial NENs were excluded. She had routine surveillance for the first 5 years with MRIs and positron emission tomography/CTs after the initial presentation which was treated with radiation followed by cisplatin and etoposide. This case highlights the difference in primary NENs versus NEN metastases to the brain, and that longer periods of surveillance are likely required for primary NENs. This is important because the prognosis between primary NENs and metastatic NENs to the brain are vastly different and should not be treated as equal diseases. The patient eventually died of her recurrence secondary to complications of a ventriculoperitoneal shunt placed for treatment of hydrocephalus from the disease.